Constructing optimal stock portfolio with Markowitz Model - Darko, Samuel (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Degree of Master of Science in Industrial Mathematics, May-2012